2013
DOI: 10.1016/j.apenergy.2012.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of finite-rate kinetics on carbon conversion in a high-pressure, single-stage entrained flow gasifier with coal–CO2 slurry feed

Abstract: Coal-CO 2 slurry feed has been suggested as an attractive alternative to coal-water slurry feed for single-stage, entrained-flow gasifiers. Previous work demonstrated the system-level advantages of gasification-based plants equipped with CO 2 capture and CO 2 slurry feed, under the assumption that carbon conversion remains unchanged. However, gasification in carbon dioxide has been observed to be slower than that in steam. In view of this, the impact of CO 2 slurry feeding on gasification kinetics and ultimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The ROM description via RNM allows for detailed finite-rate chemical kinetics but with simplified flow representation in the gasification process. A number of ROM studies for coal gasification process have been reported [11][12][13][14][15][16][17][18][19][20][21][22]. For example, Monaghan et al have developed ROMs with multiple reactors to study entrained flow gasifiers, in which the reactors are constructed based on the zero axial velocity boundaries from CFD simulations [11,12].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The ROM description via RNM allows for detailed finite-rate chemical kinetics but with simplified flow representation in the gasification process. A number of ROM studies for coal gasification process have been reported [11][12][13][14][15][16][17][18][19][20][21][22]. For example, Monaghan et al have developed ROMs with multiple reactors to study entrained flow gasifiers, in which the reactors are constructed based on the zero axial velocity boundaries from CFD simulations [11,12].…”
Section: Introductionmentioning
confidence: 98%
“…Thereafter, ROMs have been effectively used to investigate the effects of operation conditions on gasification characteristics [16][17][18][19]. Recently, dynamic ROMs with reactor volumes being adaptively adjusted according to oxygen split have been developed considering the fact that oxygen split may result in the change in flow patterns [22].…”
Section: Introductionmentioning
confidence: 99%
“…As a current technique, large‐scale coal gasification is an essential approach to using coal resource in a clean and efficient way . It is achieved via the reactions among coal, water, and oxygen in a gasifier vessel operated under a high‐pressure of 2‐8.5 MPa and a high‐temperature within 1300°C‐1600°C . In China, the annual capacity of coal gasification reached 5.1 billion cubic meters in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] It is achieved via the reactions among coal, water, and oxygen in a gasifier vessel operated under a high-pressure of 2-8.5 MPa and a high-temperature within 1300°C-1600°C. [17][18][19][20] In China, the annual capacity of coal gasification reached 5.1 billion cubic meters in 2018. Even so, it is still far below that (17 billion cubic meters per year) targeted by the government by end of 2020.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are specific cases where CO 2 is the preferred feeding gas. Contrary to nitrogen, CO 2 cannot be considered as inert; it affects the kinetics of many reactions (Botero et al, 2013(Botero et al, , 2012.…”
Section: Using Co 2 As Coal Carrier: Gasifier Modeling and Feeding Tementioning
confidence: 99%